Tailoring the acid distribution and identifying the active center of rod-shaped HSUZ-4 zeolite for enhancing dimethyl ether carbonylation performance. (1st May 2022) - Feng, Xiao-Bo; Cao, Jing-Pei; Su, Chang; He, Zi-Meng; Zhao, Xiao-Yan
Graphical abstract: Rod-shaped HSUZ-4 zeolite is discovered with distinctive activity and stability for DME carbonylation, which is dominated by the acid concentration and the number of 8-MR pore openings. Highlights: Both the surface architecture and acid distribution of HSUZ-4 zeolite can be precisely regulated. The structure-performance correlations between HSUZ-4 zeolite and carbonylation performance were systematically studied. The catalytic activity was determined by the synergistic effect of the acid concentration and the number of 8-MR pore openings. T1-O12 site located in 8-MR channel was energetically favorable for catalyzing DME carbonylation. Abstract: Carbonylation, an important reaction to realize controllable carbon chain growth by C–C coupling, is highly attractive but challenging due to the rapid deactivation behavior. HSUZ-4 zeolite is a new candidate with a high durability for catalyzing dimethyl ether (DME) carbonylation. However, its industrial application is still impeded because of the low activity. In the present paper, the activity of DME carbonylation over rod-shaped HSUZ-4 zeolite can be significantly improved by adjusting the acid distribution. Results show that the DME carbonylation performance over rod-shaped HSUZ-4 zeolite was determined by the synergistic effect of the acid concentration and the number of 8-MR pore openings. Furthermore, we firstly revealed that the carbonylation reaction occurs preferentially at T1-O12 site located in 8-MR with a quantum-chemical method. Additionally, we discovered that the activity of HSUZ-4 zeolite can be further improved by promoting the crystal growth along the c axis because more 8-MR channels are exposed. This work will provide a detailed theoretical guidance for the rational designing and fabricating more efficient catalysts for the carbonylation reaction, which is highly attractive but remains challenge for the synthesis of C2+ oxygenate chemicals from syngas and/or CO2 .